Development and Validation of a Novel Prognosis Prediction Model for Patients With Stomach Adenocarcinoma - Wang, Tong; Wen, Weiwei; Liu, Hongfei; Zhang, Jun; Zhang, Xiaofeng; Wang, Yu (Frontiers in Medicine, 2021)
Background: Stomach adenocarcinoma (STAD) is a significant global health problem. It is urgent to identify reliable predictors and establish a potential prognostic model. Methods: RNA-sequencing expression data of STAD patients were downloaded from the Gene Expression omnibus (GEO) and the Cancer Genome Atlas (TCGA) database. Gene expression profiling and survival analysis were performed to investigate differentially expressed genes (DEGs) with significant clinical prognosis value. Overall survival (OS) analysis, univariable and multivariable Cox regression analysis were performed to established the prognostic model. Protein-protein interaction (PPI) network, functional enrichment analysis, and differential expression investigation were also performed to further explore the potential mechanism of the prognostic genes in STAD. Finally, nomogram establishment was undertaken by performing multivariate cox regression analysis, and calibration plots were generated to validate the nomogram. Results: A total of 229 overlapping DEGs were identified. Following Kaplan-Meier survival analysis, univariate and multivariate Cox regression analysis, eleven genes significantly associated with prognosis were screened and five of these genes, including COL10A1, MFAP2, CTHRC1, P4HA3 and FAP, were used to established the risk model. The results showed that patients with high-risk scores have a poor prognosis, compared with those with low-risk scores (P=0.0025 for the training dataset and P=0.045 for the validation dataset). Subcequently, a nomogram (including TNM stage, age, gender, histologic grade and risk score) was created. In addition, differential expression and immunohistochemistry stain of the five core genes in STAD and normal tissues were verified. Conclusion: We develop a prognostic-related model based on five core genes, which may serve as an independent risk factor for survival prediction in patients with STAD.